PARE0002 IMPACT OF SERVICE DOGS ON THE BURDEN OF ARTHRITIS. (2nd June 2020) - Wegscheider, P.
Abstract : Background: Assistance dogs support humans with different physical disabilities: 1. Service dogs for people with diverse mobility impairments 2. signaling dogs for humans diagnosed with diabetes, hearing impairments, seizure, or posttraumatic stress disorder 3. guide dogs for people with visual impairments. Definitions and terms are not consistent over Europe; Austrian terminology is used in the following. These specially trained dogs support people in their everyday lives and make it possible that less help is required from personal assistants or caregivers. Diverse studies show this positive impact of assistance dogs on the quality of life of disabled people. There are just a few case reports from United States about service dogs for people diagnosed with any inflammatory rheumatic disorder. Dogs are trained individually for about 1.5 years before team training and the concluding team assessment through Austrian authorities take place. Since 2015, there has been an adapted legislation for service dogs in Austria which brings significant improvements in many areas. In comparison to the model set by Austria, there is no corresponding legal basis at EU level or in other European countries. Objectives: Case-report about my own situation diagnosed with juvenile idiopathic arthritis (JIA) in 2001 and my service dog May. May supports my every day live in private and business affairs since 2019 Methods: May was trained for less than two years before team assessment. May is able to pick up things I dropped. These include coins, my key, my mobile phone, clothes, towels and lots of other things I want her to pick it up for me. May opens and closes doors, empties the washing machine, pulls the laundry basket and even helps me put on and take off clothes. In general, she carries many things which I instruct her to carry. I am able to learn her more new things in a short time. Furthermore May acts safe on public transport and even airplanes. Due to special training May is allowed to move without dog leash or muzzle. A muzzle or leash would handicap the dog's work. As a result of May's help I need less personal assistance. Results: May's physical and psychological support gives me greater independence and increases my self-confidence. She was trained to specifically meet the needs of my disability. Beside her skills, May helps to reduce pain and burden of arthritis. Conclusion: My aim is to spotlight the great support of service dogs to severely affected arthritis patients. Austria had realized legislation for assistance dogs to guarantee certain permissions the owner's needs (e.g. access to working place, hospital). I would love to raise awareness about assistance dogs to improve the knowledge about those animals to implement European legislation. References: [1]Arbeitskreis für Hygiene in Gesundheitseinrichtungen des Magistrats der Stadt Wien, MA 15, Richtlinie für den Umgang mit Assistenzhunden und Therapiehunden in Gesundheitseinrichtungen, 29.3.2017; access 1.10.2019 [2]AK Krankenhaushygiene OÖ, Umgang mit Assistenzhunden in Gesundheitseinrichtungen, Version 1; access 1.2019 [3]Bremhorst, A et al, Spotlight on Assistance Dogs- Legislation, Welfare and Research, Animals 2018, 8, 129; doi:10.3390/ani8080129 [4]Deutsche Gesellschaft für Krankenhaushygiene (DGKH), Empfehlungen zum hygienegerechten Umgang mit Therapiehunden in Krankenhäusern und vergleichbaren Einrichtungen, Hyg Med 2017; 42-10 [5]Glenk, LM et al, Perceptions on Helath Benefits of Guide Dog Ownership in an Austrian Population of Blind People with and without a Guide Dog, Animals 2019, 9, 428; doi:10.3390/ani9070428 [6]Lundqvist, M et al, Certified service dogs- A cost- effectiveness analysis appraisal, Plos ones 12.9.2019, doi:10.1371/journal.pone.0219911 [7]Sozialministeriumservice, Richtlinie Therapiehunde des Bundesministers für Arbeit, Soziales und Konsumentenschutz, 01.01.2015; access 1.10.2019 Acknowledgments: I am very grateful to Kati Kohoutek, May's trainer and the efforts of Austrian's long lasting dog trainers and Karl Weissenbacher, the leader of Messerli Institute/ department of Veterinary University Vienna. Disclosure of Interests: None declared